Divinity and state - Womersley, David (Oxford University Press, 2010)
This text explores how the Reformation's transformation of religious belief into a political statement and the saturation of the national past with religious implications (created by the political developments of the 1530s) was reflected in 16th-century English historiography and historical drama.